A ligand conformation preorganization approach to construct a copper–hexacarboxylate framework with a novel topology for selective gas adsorption. Issue 1 (10th December 2018) - Wang, Yao; He, Minghui; Gao, Xiaoxia; Wang, Xia; Xu, Guohai; Zhang, Zhengyi; He, Yabing
Abstract : A ligand conformation preorganization strategy was employed to design a hexacarboxylate ligand, and its corresponding copper-based MOF was constructed, exhibiting a novel topological structure and the potential for the separation and purification of acetylene and natural gas. Abstract : The development of porous MOFs with novel structures and functional properties is a key research topic in the MOF chemistry and materials field. In this article, by employing a ligand conformation preorganization strategy, we designed a nonplanar methyl-substituted triisophthalate ligand, which was used to successfully construct a copper–hexacarboxylate framework with a novel topological structure. More importantly, the obtained MOF not only exhibits good hydrolytic stability but also shows utility as an adsorbent for efficient separation and purification of C2 H2 and natural gas under ambient conditions. At ambient temperature and atmospheric pressure, the C2 H2 and CO2 uptake capacities reach up to 149.1 and 83.1 cm 3 (STP) g −1, while the IAST-predicted C2 H2 /CH4 (50/50, v/v), C2 H2 /CO2 (50/50, v/v), and CO2 /CH4 (50/50, v/v) adsorption selectivities are as high as 22.2, 3.81, and 5.13.